Synthesis of the Algorithm of Adaptive Compensation of Nonlinear Distortions for Informational Systems - Shefer, Oleksandr; Shulha, Oleksandr; Ichanska, Nataliia; Kozelkova, Caterina (International Journal of Engineering and Technology, 2018)
An adaptive method of compensation of non-linear distortions was created in informational systems on the basis of usage the synthesized non-linear adaptive compensators for the expansion of a linear dynamic diapason of radio receiving devices that differs from the well-known ones, because it doesnâ€™t lead to reduction of reliability of telecommunication systems both in apparatus and in functional meaning that allowed to increase the quality of their functioning. The usage of non-linear adaptive compensators allows getting the necessary meanings of parameters and the methods of connection of devices that are set to depress the non-linear distortions in those mentioned systems that will allow increasing the reliability of functioning of informational systems in 12% in general.Â Â Â